(3QSGdI GdGHGfI hGdJUQjM aj eYfi UdGI GdJSHjMs - (3TQa GdOjf LYaQ Hf eMeO Hf MeRIs ((3GSeGYjd CMeO Hf CMeO GeSGYjd GdbjQi s)
(3ChdgG (B:s
(3GdMeO ddg GdeJYGdi Yf OQc GdGHUGQ hHYO aEf fYe Gddg GdLSGe hfYe GhdjGFI Ydjge GaVd GdSdGe hfYe OQhOg GdJhGe YfO GOfi YHjOge s
(3BNQgG (B:s
(3SdGekG eJUdkG Edi jhe GdbjGeI MSHfG Gddg hfYe Gdhcjd hfYe Gdehdi hfYe GdfUjQ s
(3HgG fXGe GdJYbjHIs
(3jfbU hQbI Qbe (B77s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs